1998
DOI: 10.1139/x97-213
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast microsatellites as markers for paternity analysis in Abies alba

Abstract: This study describes the application of previously characterized chloroplast microsatellites as markers for paternity analysis in a conifer species. The investigations were performed on silver fir (Abies alba Mill.) relic trees in an endangered population of the Ore Mountains (Germany). Two relatively isolated adult trees about 30 m apart, as well as 24 naturally regenerated young trees in their direct neighborhood, were analyzed at two chloroplast microsatellite loci. Results reveal the potential usefulness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…Its generally uniparental mode of inheritance makes it a powerful tool to elucidate relative contributions of seed and pollen flow to the genetic structure of natural populations by comparison with nuclear markers. Whilst nuclear microsatellites are the marker system of choice for genetic diversity, genome mapping, DNA fingerprinting and parentage analysis, chloroplast microsatellites (cpSSRs) revealed to be of special value in studies of plant population geographic structure and differentiation [2,7,20] and for paternity analysis in the specific case of conifers [30]. However, as for nuclear microsatellites, a high level of homoplasy (alleles identical in size but not necessarily identical by descent due to convergent mutations) is expected [11].…”
Section: Introductionmentioning
confidence: 99%
“…Its generally uniparental mode of inheritance makes it a powerful tool to elucidate relative contributions of seed and pollen flow to the genetic structure of natural populations by comparison with nuclear markers. Whilst nuclear microsatellites are the marker system of choice for genetic diversity, genome mapping, DNA fingerprinting and parentage analysis, chloroplast microsatellites (cpSSRs) revealed to be of special value in studies of plant population geographic structure and differentiation [2,7,20] and for paternity analysis in the specific case of conifers [30]. However, as for nuclear microsatellites, a high level of homoplasy (alleles identical in size but not necessarily identical by descent due to convergent mutations) is expected [11].…”
Section: Introductionmentioning
confidence: 99%
“…Paternal inheri-tance of chloroplast genomes in most conifers (Neale, Wheeler, and Allard, 1986;Neale and Sederoff, 1989) makes chloroplast microsatellites particularly effective markers for studying mating systems, gene flow via both pollen and seeds, and uniparental lineage. Predominant paternal inheritance of chloroplast DNA has been demonstrated in European Abies with previously characterized (Vendramin et al, 1996) Pinus thunbergii primers at two highly variable microsatellite loci (Vendramin and Ziegenhagen, 1997;Ziegenhagen et al, 1998;Vendramin et al, 1999). Intraspecific diversity and population structure in heterologous amplification with these primers have been demonstrated in many pine species as well (Morgante and Olivieri, 1993;Powell et al, 1995a;Cato and Richardson, 1996;Vendramin et al, 1996;Morgante, Felice, and Vendramin, 1998).…”
mentioning
confidence: 96%
“…Chloroplast microsatellite has been used for analyzing genetic diversity in genus Olea (Filizi and Koc, 2012), maritime pine (Ribeiro et al, 2001), Solanaceous plants (Bryan et al, 1999), Pinus radiata (Cato and Richardson, 1996), soybean (Xu et al, 2002) and Sorbus L. (King and Ferris, 2000). Studies of the inheritance using chloroplast microsatellite also have been reported in Fraxinus (Morand-Prieur et al, 2002), Abies alba (Ziegenhagen et al, 1998) and Helianthus annuus (Wills et al, 2005). Stoehr et al (1998) and Fernandes et al (2008) applied cpDNA marker to the seed orchard management.…”
Section: Application Of the Results For The Breeding Program And The Fmentioning
confidence: 99%